COVID-19 – a Five-Year Update - Ahmed Burooj (ImmunoAnalysis)
Background: This review aims to categorically describe novel advancements to our understanding and management of COVID-19 and associated short- and long-term sequelae such as Long COVID. Methods: Indexing services (Scopus and PubMed) were used to identify pertinent studies, prioritizing original research, meta reviews and updated institutional guidelines from 2022 onwards. Papers not published in English (or where full-text translation was not available), those skewed in terms of gender distribution of participants, conducted on non-human populations and proposal and opinion papers were excluded. For the purposes of this paper, Long COVID was taken to mean the persistence of symptoms longer than 8 weeks after an acute COVID-19 infection. After deduplication, application of the exclusion criterion and checking for relevance, 52 sources were identified for this review. The keywords used for this literature search were COVID-19, Long COVID, Chronic COVID, SARS-CoV-2. Results: New COVID-19 variants challenge vaccine efficacy, highlighting socioeconomic disparities in vaccination rates. Long COVID exhibits complex symptoms, including cognitive decline and physical health impacts. The virus’s affinity for ACE-2 receptors suggests broader health implications, including reproductive and metabolic disorders. COVID-19 can cause a drop in IQ proportional to severity of disease experienced. Conclusion: COVID-19’s multifaceted health impacts necessitate ongoing research and targeted interventions. Addressing socioeconomic disparities, updating vaccine formulations, and understanding long-term effects are crucial. Equitable healthcare policies are essential to mitigate COVID-19’s global health threat and inform future strategies.